EFFECT OF ARTIFICIAL RAISING TEMPERATURE ON ZOOXANTHELLAE DENSITY, LIPID CONTENT, LIPID CLASS, FATTY ACID, MALONDIANDEHIT AND CHLOROPHYLL COMPOSITION OF SOME VIETNAMESE CORAL SPECIES - Son, Nguyen Van; Long, Pham Quoc; Quan, Pham Minh; Hai, Ha Viet; Thuy, Tran Thu; B., Imbs A. (Vietnam Journal of Marine Science and Technology, 2014)
There is a close symbiotic relationship between zooxanthellate corals and their symbionts, zooxanthellae. Zooxanthellae may provide up to 90% of total energy for corals; while they get nutrients, shelter, and protection from host corals. Due to high temperature stress, corals lose their symbionts and die. This phenomenon is called coral bleaching. It is believed that the coral bleaching is related to the biochemical compositions in corals. In this study, we determined the zooxanthellae density as well as the change of lipid content, lipid class and fatty acid composition between healthy and bleached corals. The results showed that zooxanthellae density steadily reduced during the coral bleaching. When corals were beached, half of total lipid contents of corals lost. There was no significant change in the relative percentage of structural and storage lipids. However, there was remarkable change in the fatty acid composition. Completely bleached corals contained a significantly lower amount of polyunsaturated fatty acids (PUFAs), but higher amount of saturated fatty acids (SAFAs) and monounsaturated fatty acids (MUFAs) than those in healthy corals.